Structural Stability of ADTC5 Peptide: Conformational Insights into Dynamics and Its Binding Mode - Parsaoran Siahaan; Vivitri Dewi Prasasty; Bungaran David Simanjuntak; Suci Hildayani; Khairul Anam (Journal of Tropical Life Science, 2017)
The cyclic structure of ADTC5 (Ac-CDTPPVC-NH2) peptide is known has ability to modulate homo dimer E-cadherin interactions to form adherens junction at the intercellular junction.Â The ability to inhibit E-cadherin interaction has become important to increase paracellular porosity in delivering drug molecules to the target cell. There are two types of ADTC5 state: opened-cyclic state (OCS) and closed-cyclic state (CCS). OCS of ADTC5 is affected by distance constraint and CCS is formed by disulfide bond from terminal cysteines through force restraint. The aim of this research is to investigate the inhibition activity of ADTC5 peptide upon E-cadherin. Here we used molecular docking and molecular dynamics approaches. The structure of ADTC5 peptide was generated by PyMOL program. GROMACS v4.5.5 was utilized to simulate molecular dynamics. The optimized ADTC5 molecule was placed in aqueous or polar condition at physiological pH. Furthermore, ADTC5 was docked with EC1-EC2 coupled domain of E-cadherin using AutoDock 4.2 and be refined using molecular dynamic (MD). The result showed that CCS ADTC5 peptide has stronger affinity and more stable interaction with EC1-EC2 coupled domain than the OCS one.